Rock Salt Production From Northeastern Thailand - , Laowattanabandit, P ([Yogyakarta] : Departmentof GeologicalEngineering,Facultyof Engin, 2009)
Every day, each of planet earth's 6 billion inhabitants uses salt. We need a small amount of salt to survive. Over the past century the annual production of salt worldwide has increased from 10 million tonnes to over 200 million tonnes today. Salts can be separated mainly into 2 types, namely sea salt and rock salt according to their ongm. A huge amount of rock salt has been found underneath the northeastern region of Thailand. Salt has been produced from brine in this region for several decades. Thailand is the major exporter of rock salt in Southeast Asia. This paper will present geology of rock salt underneath northeastern Thailand. Various methods to produce rock salt are extensively demonstrated along with the effect of rock salt production. Solution mining has been proposed to improve efficiency of rock salt production from northeastern Thailand.